THE INFLUENCE OF ROA, ROE, ROS, AND EPS ON STOCK PRICE - Manoppo, Carmela Pinky (Universitas Sam Ratulangi, 2015)
In a competitive business environment, the use of size financial performance fundamental to the analysis of financial ratios as conventional accounting gauges, such as profitability ratios have major drawbacks are ignoring their capital costs making it difficult to know whether a company has managed to create value or not. By using a multiple linear as a data analysis tools, this research found that ROA, ROE, ROS and EPS have significant influence on Stock Price, simultaneously and partially. The company need to improve the ROA, ROE, ROS, and EPS to enhance the stock price. Keywords : roa,roe, ros, eps, stock price